Surgical Management of Atypical Scheuermann's Disease with Spinal Cord Compression: Reporting a Rare Case and Literature Review - Ghosh, Ankan; Dasgupta, Sibaji; Datta, Gitanjali; Sadique, Shahid Iftekhar; Majhi, Sri Krishna; Chaudhuri, Shubhamitra; Tiwari, Varun; Sharma, Bhaskar; Nayak, Rakesh Kumar; Ghosh, Subhasis; Yangi, Kivanc; Bozkurt, Ismail; Chaurasia, Bipin (Asian Journal of Neurosurgery, 2025)
Atypical Scheuermann's disease is a rare spinal disorder characterized by progressive kyphotic deformity and, in rare instances, spinal cord compression. Unlike classic Scheuermann's disease, which affects the thoracic spine, atypical variants may involve the thoracolumbar or lumbar regions, leading to neurological compromise. This report presents a rare case of atypical Scheuermann's disease with spinal cord compression, its surgical management, and a review of relevant literature. A 24-year-old male presented with progressive lower limb weakness, gait instability, and back pain for 6 months. Neurological examination revealed spastic paraparesis, hyperreflexia, and sensory deficits below the affected spinal level. Imaging studies, including magnetic resonance imaging and computed tomography, demonstrated a severe thoracolumbar kyphotic deformity with vertebral wedging, disc degeneration, and posterior ligamentous hypertrophy leading to significant spinal cord compression. Considering the progressive neurological deficits, the patient underwent posterior decompression, deformity correction, and instrumented fusion. A pedicle subtraction osteotomy was performed to restore sagittal alignment, followed by posterior spinal stabilization using pedicle screw fixation. Postoperatively, the patient showed gradual neurological improvement with enhanced motor function and pain relief. At the 6-month follow-up, the patient exhibited significant recovery in motor function and ambulation. Radiological evaluation confirmed adequate correction of kyphosis and stable spinal instrumentation. Rehabilitation continued with physiotherapy to improve strength and balance. Atypical Scheuermann's disease with spinal cord compression is exceedingly rare, necessitating early diagnosis and timely surgical intervention to prevent irreversible neurological deficits. This case highlights the role of posterior decompression, osteotomy, and fusion in achieving favorable outcomes. A literature review underscores the importance of individualized surgical planning based on severity, neurological status, and spinal alignment. Early recognition and surgical intervention are crucial in managing atypical Scheuermann's disease with spinal cord compression. Posterior decompression and instrumented fusion effectively restore function and prevent long-term disability.
Keywords: atypical Scheuermann's disease; spinal cord compression; posterior decompression; thoracic kyphosis